UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI IMPLEMENTASI PEMBELAJARAN KOOPERATIF DENGAN TUTOR SEBAYA - Nani Zulhani (Universitas Muhammadiyah Bengkulu, 2019)
This study aims to determine the increase in learning outcomes of class VIII.F SMP Negeri 2 Kota Bengkulu in the academic year 2017-2018 in solving questions on SPLDV material through the implementation of cooperative learning with peer tutors.The subjects of this study were 34 students of VIII.F of SMP Negeri 2 Kota Bengkulu. Data collected includes: student learning outcomes, teacher observation results, student observation results. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle includes 4 (four) stages, namely: planning, action, observation (observation) and reflection. In this study it is said to be successful if at least 75% of students get a value of ≥60.The results of this study shows that the first cycle of learning outcomes is not yet appropriate with the expectation. There are only 55,88% of students who reach completeness. It means that the indicator of success has not been achieved, while in cycle II shows thatlearning outcomes are in line with expectations. There are 88,24% of students who reach completeness. It means that indicators of success have been achieved.Based on the analysis of the research results it can be concluded that through the implementation of cooperative learning with peer tutors can improve the learning outcomes of grade VIII.F SMP Negeri 2 Kota Bengkulu in the school year 2017-2018 in solving questions on SPLDV material. Thus it is recommended that Mathematics teacher associates in the teaching and learning process use cooperative learning models with peer tutors so that student learning outcomes are better. Keywords: learning outcome, peer tutors